Analisis Sentimen Terhadap Film Sri Asih Dengan CNN, KNN, dan Logistic Regression - Wijaya, Ester Caroline Dwi Wijaya; Hendry (LPPM Universitas Potensi Utama, 2023)
Technological developments have had a significant impact on various sectors, which is in the film industry, of course this is become a challenge for film producers to make works that suit people's tastes. The recent film that has become the public's attention is the Sri Asih film, due to its fresh genre and story, this film got a lot of opinions from the public. With the social media Twitter, people can express their opinions, comments, and criticisms online. Therefore, Twitter can be used to observe positive and negative responses to analyze public opinion about the film Sri Asih. The analysis is sentiment analysis, which is a process to analyze whether public opinion is negative, neutral, or positive. The goal of this study is to determine the public's response to the Sri Asih film which can be used as an evaluation for film producers. This research was conducted using three methods: Convolutional Neural Network (CNN) with 78% accuracy, K-Nearest Neighbor (KNN) with 61% accuracy, and Logistic Regression with 81% accuracy.